Changing the Change as a Source of Value Creation not Being a Root of Employee Stress - Sharma, Sonika (Journal of Commerce and Trade, 2011)
Linkages amongst the components of an organisation and their constant and energetic interactions are of elemental importance to management researchers and practitioners. Throughout most sectors of the economy, a sense pervades that the party is over. While for few this appears to be true but for many the party is never over except the change of dimension. One of the dangers the companies fall in this scenario and even in some turnarounds is the near panic over what it will take to keep a team focused and in their seat. Generally speaking, organisations do not change in this way but that has not been fatal to this paradigm. Instead, accepting it without challenge, people rush around trying to find new tricks for making things happen which leads to employee stress. Nevertheless the economic downturn is now a topic of discussion in boardrooms, classrooms, cocktails, gossip groups and even among friends getting together casually but people hardly discussed it as a change. The change which led to suicides by many who lost their jobs, many remained under stress for quite a long time and almost every employee was under stress for some time. The question arises how we can change the change so that it becomes a source of value creation instead of a cause of employee stress? To answer this all the present paper has been attempted which focuses on three key aspects.